1974
DOI: 10.1111/j.1365-2621.1974.tb01782.x
|View full text |Cite
|
Sign up to set email alerts
|

Post mortem changes and spoilage in rock lobster muscle

Abstract: Glycolysis in rock lobster comprising the oblique extensor, oblique flexor and enveloping muscles of Jasus novae-hollandiae was studied under anaerobic conditions at ZOO, 15" and 0°C. After bisecting the muscles along the mediosaggital plane one section was treated by dipping for 4 min in 3% sodiumThe following abbreviations are used in this paper: ATP, adenosine 5'-triphosphate; ADP, adenosine 5'4-phosphate; PEP, phosphoenolpyruvate; NAD+ and NADH, oxidized and reduced forms of nictotinamide-adenine dinudeoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1974
1974
2005
2005

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 38 publications
(3 reference statements)
0
4
0
Order By: Relevance
“…Post mortem glycolytic studies reported earlier (Sidhu et al, 1974) showed that breakdown of phosphoarginine and ATP was greatly reduced when the temperature of rock lobster muscle was lowered from 15" to 0°C. Consequently, as long as the energy supply of the muscle cell in the form of ATP is not exhausted, the cell can maintain its integrity and retain amino acids and other solutes in its internal environment, thus denying easy access of nutrients to spoilage bacteria.…”
Section: Amino Acidrmentioning
confidence: 86%
See 3 more Smart Citations
“…Post mortem glycolytic studies reported earlier (Sidhu et al, 1974) showed that breakdown of phosphoarginine and ATP was greatly reduced when the temperature of rock lobster muscle was lowered from 15" to 0°C. Consequently, as long as the energy supply of the muscle cell in the form of ATP is not exhausted, the cell can maintain its integrity and retain amino acids and other solutes in its internal environment, thus denying easy access of nutrients to spoilage bacteria.…”
Section: Amino Acidrmentioning
confidence: 86%
“…Methods of keeping rock lobsters and preparation of muscle samples have been described in Part I of this paper (Sidhu et al, 1974). In the present studies, abdominal muscles were bisected along the mediosaggital plane, and one section of each was dipped in 15 ppm of oxytetracycline in 3% sodium chloride solution at room temperature (treated) for 4 min while the other was dipped in 3% sodium chIoride solution for the same period (untreated).…”
Section: Rock Lobster and Firefaration Of Materialsmentioning
confidence: 99%
See 2 more Smart Citations